Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen pada Dippo 88 Cafe Lubuk Pakam - Sri Tita Wahana; Yuni Asri Ningratri (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether there is an influence of service quality and price on consumer satisfaction at Dippo 88 Cafe Lubuk Pakam. The sample in this study were 95 people. The sampling technique used accidental sampling, namely the determination of samples based on coincidence, consumers who incidentally / incidentally meet with researchers can be used as samples, if viewed by people who happen to be found suitable as a source of data. Data analysis used Multiple Regression test, hypothesis testing using the coefficient of determination (R2), partial test (t test) and simultaneous test (F test), while processing data using SPSS20. The results of this study indicate that service quality and price are able to explain its existence to the variable customer satisfaction, in addition partially the quality of service does not affect customer satisfaction, and price has a positive and significant effect on customer satisfaction. While simultaneous service quality and price have a positive and significant effect on customer satisfaction at Dippo 88 Cafe Lubuk Pakam.